Challenges for Assessing the Influence of Spirituality in Moral Development – In Searching for a Scale (Global Journal of Human-Social Science, 2024)
This article aims to examine approaches to the assessment and measurement of spirituality to establish correlations with moral development and ethical education The methodology employed consisted of a literature review conducted in the databases of CAPES SCIELO BDTD and Google Scholar The results of this research revealed the existence of 50 measures intended for the assessment of spirituality and religiosity Among these measures the stages of Fowler s Faith and the PCBS stand out both selected for detailed analysis due to their proximity to the assessment and measurement of spirituality as well as their relevance in the moral and educational context However it is prudent to consider that the development of a more specific scale focused on spirituality moral development and education is still necessary to address the nuances and particularities of the Brazilian reality
Keywords: spirituality; religiosity; morality; education; measures